Superconducting Ti15Zr15Nb35Ta35 High-Entropy Alloy With Intermediate Electron-Phonon Coupling - Yuan, Yuan; Wu, Yuan; Luo, Huiqian; Wang, Zhaosheng; Liang, Xue; Yang, Zhi; Wang, Hui; Liu, Xiongjun; Lu, Zhaoping (Frontiers in Materials, 2018)
The body-centered cubic (BCC) Ti15Zr15Nb35Ta35 high-entropy alloy showed superconducting behavior at around 8 K. The electronic specific heat coefficient and the lattice specific heat coefficient β were determined to be γ=9.3±0.1 mJ/mol K2 and β=0.28±0.01 mJ/mol K4, respectively. It was found that the electronic specific heat Ces does follow the exponential behavior of the Bardeen-Cooper-Schrieffer (BCS) theory. Nevertheless, the specific heat jump (ΔC/γTc ) at the superconducting transition temperature which was determined to be 1.71 deviates appreciably from that for a weak electron-phonon coupling BCS superconductor. Within the framework of the strong-coupled theory, our analysis suggests that theTi15Zr15Nb35Ta35 HEA is an intermediate electron-phonon coupled BCS-type superconductor.